The influence of knowledge management and leveraging of intellectual capital on the organization performance: A case study of Telekom Malaysia - Ismail, Mazlan; Songip, Ahmad R. (2006)
This paper investigates the influence of Knowledge Management and Leveraging of Intellectual Capital on the performance of Telekom Malaysia. The study was conducted through questionnaire survey of 400 Telekom Malaysia (TM)’s executives from the TM’s headquarters and all the state business areas.The dependent variable is the performance of TM which includes the operating efficiency, business performance, organisational leadership and business leadership.The independent variables are knowledge management, intellectual capital and leveraging of the intellectual capital.Relevant statistical techniques such as regression and correlation test, factor analysis and ANOVA are used in t his study.It was found that knowledge management has an indirect influence to the performance whereas leveraging the intellectual capital has the greatest positive influence to the performance.The results of this study have significant contribution to TM’s strategy in managing, leveraging and develop the intangible asset for a sustainable overall performance of TM.